Servant leadership and its impact on social loafing: organizational happiness as moderating - Ali Salih, Ahmad; Hijazin, Areej Faeik (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to explore the impact of servant leadership on social loafing, with existence of organizational happiness as a moderator variable. The field of this study was private hospitals in the city of Amman. The population (4,727). The sample of this study was selected using the Systematic Random Method, the total sample size is (357) field nurses. A questionnaire was used as tool for collecting data, and out of the total (360) distributed questionnaires, (289) were accepted, which represent (% 81) of the total distributed questionnaires. The collected Data was analyzed by a set of statistical methods, (Means, Standard Deviations, Cronbach’s Alpha, T-test, Confirmatory Factor Analysis (CFA), Exploratory Factor Analysis (EFA), Pearson Correlation Coefficient, Skewness and Kurtosis Coefficients, Kolmogorov-Smirnov, VIF, Tolerance, Structured Equation Model (SEM) using SMART-PLS 3 software, and Hierarchical Integration Regression).Result shows servant leadership has negative impact on social loafing, furthermore it was found that the organizational happiness as a moderator increases the negativity of the impact of servant leadership on social loafing. The study concluded increasing the practices of servant leadership has an influential contribution to reducing social loafing behaviors, and entering organizational happiness, will increase the negativity influences, which decreases the behaviors of social loafing.